Assessing Dietary Intake in Childhood Cancer Survivors. Issue 4 (October 2015) - Zhang, Fang Fang; Roberts, Susan B.; Must, Aviva; Wong, William W.; Gilhooly, Cheryl H.; Kelly, Michael J.; Parsons, Susan K.; Saltzman, Edward
<x xml:space="preserve">Abstract</x> ABSTRACT Cancer diagnosis and treatment may influence dietary intake. The validity of using self-reported methods to quantify dietary intake has not been evaluated in childhood cancer survivors. We validated total energy intake (EI) reported from Food Frequency Questionnaire (FFQ) and repeated 24-hour diet recalls (24HRs) against total energy expenditure (TEE) measured using the doubly labeled water method in 16 childhood cancer survivors. Dietary underreporting, assessed by (EI−TEE)/TEE × 100%, was 22% for FFQ and 1% for repeated 24HRs. FFQ significantly underestimates dietary intake and should not be used to assess the absolute intake of foods and nutrients in childhood cancer survivors.